1998
DOI: 10.1021/ic9712333
|View full text |Cite
|
Sign up to set email alerts
|

Speciation in Vanadium Bioinorganic Systems. 5. Interactions between Vanadate, Uridine, and ImidazoleAn Aqueous Potentiometric, 51V, 17O, and 13C NMR Study

Abstract: The full speciation has been determined in the aqueous vanadate-uridine (UrH 2 ) and vanadate-uridine-imidazole (ImH) systems. The studies performed allow direct comparison with the corresponding adenosine systems, and the role of the pyrimidine and purine bases on various complex properties could be evaluated. The studies also provide insight into possible biological mechanism of action. Formation constants have been determined in 0.600 M Na(Cl) medium at 25°C in the pH range 2-11, using a combination of pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 35 publications
1
45
1
Order By: Relevance
“…It has to be noted that Table 1a does not list any isomers in the V-Ur system, because we were unable to determine their formation constants in the physiological medium. We know, however, from previous NMR studies in 0.600 M Na(Cl) medium that isomers of the dominant V 2 Ur 2À 2 species do exist [52]. This can also be seen by the asymmetrical shape of the V 2 Ur 2 resonance in the physiological medium.…”
Section: Table 1amentioning
confidence: 90%
“…It has to be noted that Table 1a does not list any isomers in the V-Ur system, because we were unable to determine their formation constants in the physiological medium. We know, however, from previous NMR studies in 0.600 M Na(Cl) medium that isomers of the dominant V 2 Ur 2À 2 species do exist [52]. This can also be seen by the asymmetrical shape of the V 2 Ur 2 resonance in the physiological medium.…”
Section: Table 1amentioning
confidence: 90%
“…This is planned for the near future. Another interesting option will be the use of NMR or ESR spectroscopy on the different chromatographic fractions to try to identify the different ligands and to establish the oxidation state of vanadium in the different complexes [36,37].…”
Section: Fractionation Of Vanadium Complexes In Tissue Homogenatesmentioning
confidence: 99%
“…Moreover, the aqueous chemistry of vanadium (V), studied by several authors (Crans et al, 2004;Elvingson et al, 1998), inferred the presence of many species as a function of the solution's pH. It was suggested that pervanadyl or dioxovanadium cation (VO 2 + ) is the main species formed in the lower pH range (0.5 1.3) (Baes and Mesmer, 1976).…”
Section: Introductionmentioning
confidence: 99%